The burden of myasthenia gravis – highlighting the impact on family planning and the role of social support - Stein, Maike; Grittner, Ulrike; Stegherr, Regina; Gerischer, Lea; Stascheit, Frauke; Hoffmann, Sarah; Herdick, Meret; Legg, David; Marbin, Derin; Meisel, Andreas; Lehnerer, Sophie (Frontiers in Neurology, 2023)
Background Myasthenia gravis (MG) is a rare autoimmune disease and chronic condition that necessitates specialized care. Patients experience a significant burden of disease affecting various aspects of their lives. The aim of this study was to investigate the impact of MG on family planning, challenges associated with pregnancy, childcare responsibilities and the extent to which MG patients perceive and utilize social support. Methods This analysis used data from our main data of a large cross-sectional study built on a questionnaire-based survey encompassing 1,660 MG patients and members of the German Myasthenia Association (Deutsche Myasthenie Gesellschaft), and focused on sociodemographic, clinical and family planning relevant data points. Results Decisions regarding family planning were significantly impacted for individuals with MG when MG symptoms started either before or during their family planning (men: n = 19 and 29.7%; women: n = 156 and 58.4%). In this subgroup a substantial proportion opted against parenthood due to MG (men: n = 8 and 50.0%; women: n = 54 and 38.0% and/or another n = 12 and 8.4% of female participants encountered partner-related refusals). In the subgroup of female SP with MG starting before or during family planning who have reported ever been pregnant the self-reported miscarriage rate was 29.0% (n = 51). MG patients with medium incomes or moderate disease severity reported lower levels of perceived social support. 42.7% (n = 606) of participants needed assistance in negotiations with health insurers and 28.0% (n = 459) needed support for transportation to medical appointments. Conclusion This study shows a significant impact of MG on family planning decisions, affecting both women and men, and often resulting in life-altering decisions such as voluntary childlessness due to MG. The significance of social support becomes evident as a vital factor, especially when navigating through the healthcare system. Tailored healthcare approaches, organized guidance and comprehensive support is needed to enable informed decision-making and offer assistance for MG patients. Clinical trial registration https://clinicaltrials.gov/study/NCT03979521, Registered 7 June 2019 (retrospectively registered).